(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years Higher Education Institutions are expanding at high speed in India. The insights of higher education in India which comes from All India Survey on Higher Education (AISHE) Report 2017 distributed by MHRD clears that Gross Enrollment Ratio (GER) of Higher Education in India (HEI) is 25.8%, which is determined to the age bunch 18-23 is exceptionally low with correlation with different nations. The Indian education framework is going through changes and significant changes activities are taken by Indian Government. In this completive climate Universities need to discover better approaches to advance them for the forthcoming students. Colleges are embracing internet marketing channels over disconnected. Digital marketing is a stage for social, business commitment of customer across the world utilizing refined instruments like SEO, online journals, audits, viral marketing, show advertisements, web-based media pop-up messages which can make digital enjoyment.